Relationship between Psychological Distress and Demographic Characteristics among Patients Undergoing Coronary Artery Bypass Graft (CABG) Surgery - Noor Hanita, Zaini; Khatijah Lim, Abdullah *; Raja Amin, Raja Mokhtar; Karuthan, Chinna; Shahrul, Bahyah Kamaruzzaman (MDPI, 2022)
Coronary artery bypass graft (CABG) surgery patients often present with anxiety and depression. These symptoms coupled with pain are major concerns and are widely reported among CABG patients. The study aimed to evaluate the relationship between psychological distress and patients’ demographic data. This cross-sectional study in which 178 patients from a surgery ward were selected using the census method. Data were collected using the Hospital Anxiety and Depression Scale and the Brief Pain Inventory (Short Form). The participants’ mean age was 57.49 ± 13.78 years. The majority of participants had a moderate level of anxiety (89.3%) and a moderate level of pain interference (74.7%). Significant differences were noted, with a higher proportion of moderate anxiety level participants aged between 60 and 74 years old, married, and with a tertiary level education (p < 0.05) being found. There were also significant differences between gender (p < 0.05) and pain severity (p < 0.01) across the levels of depression. The levels of anxiety, depression, and pain were significant, especially among older patients. These symptoms should be routinely assessed, and further identification of predictors such as socioeconomic status before the procedure is necessary.